Sports Facility Management and Athlete Satisfaction: A Study at GGM Talaga Manggung Majalengka - Sahudi, Udi; Rustandi, Endi; Priyono, Ali; Purnama, Yudhi; Rudiana, R. Dadan Pra (Indonesian Journal of Sport Management, 2025)
Efficient sports infrastructure management is essential in facilitating optimal athletic performance and enhancing user experience. However, many regional sports complexes often lack a management strategy that prioritizes user-centered principles, which in turn affects the quality of service delivery and athlete satisfaction. This study aims to investigate the correlation between sports facility management practices and athlete satisfaction levels at GGM Talaga Manggung, located in Majalengka Regency. Using a quantitative descriptive approach, data collection was conducted through a structured Likert-scale questionnaire administered to a sample of 100 athletes involved in volleyball, basketball, and futsal disciplines. Data analysis used descriptive statistical techniques to assess variables such as maintenance efficacy, cleanliness standards, accessibility, service quality, and adequacy of facilities. The results indicated that overall management practices were considered adequate; however, certain aspects—namely equipment availability and inclusiveness features—required significant improvement. The highest level of satisfaction was related to safety and comfort parameters, while the provision of additional equipment received the lowest rating. The findings indicated that athlete satisfaction was positively affected by cleanliness, security, and staff responsibility, but was negatively affected by lack of infrastructure and resource constraints. The study underlines the importance of infrastructure development strategies, equitable resource allocation for equipment, and integration of inclusive design elements. It is recommended that facility administrators adopt participatory governance frameworks, improve protocol maintenance, and incorporate user feedback mechanisms to optimize service quality and enhance athlete development.